Impact of Literacy Interventions on Reading Skills in Low‐ and Middle‐Income Countries: A Meta‐Analysis. Issue 2 (18th January 2019) - Kim, Young‐Suk G.; Lee, Hansol; Zuilkowski, Stephanie S.
Abstract : Reading skills are foundational for daily lives, academic achievement, and careers. In this study, we systematically reviewed literacy interventions in low‐ and middle‐income countries, and estimated their effects on children's reading skills using a meta‐analytic approach. A total of 67 studies ( N = 213, 464) from 32 countries found in various databases (e.g., PsycINFO, ERIC) and sources (e.g., United States Agency for International Development) met our inclusion criteria. The results revealed an overall effect of .30 across various literacy outcomes. Effects varied for different outcomes, such that largest effects were found in emergent literacy skills (e.g., .40) and the smallest effects in reading comprehension (.25) and oral language skills (.20). Effects also varied as a function of other features such as teacher training support.